2‐Dimensional Materials: Electrocatalytic Water Splitting and CO2 Reduction: Sustainable Solutions via Single‐Atom Catalysts Supported on 2D Materials (Small Methods 9/2019). Issue 9 (9th September 2019) - Kwon, Ki Chang; Suh, Jun Min; Varma, Rajender S.; Shokouhimehr, Mohammadreza; Jang, Ho Won
Abstract : In article number1800492 by Mohammadreza Shokouhimehr, Ho Won Jang, and co‐workers, the recent achievements in catalytic reaction of single‐atom catalysts (SAC) supported on 2D materials are summarized. Particularly, the roles of introduced 2D materials as supporting layers in enhancing the electrochemical performance of various catalytic reactions are highlighted. This study provides clues to develop advanced energy‐conversion technologies.